The Effect Of Foreign Debt, Gold Prices And Interest Rates On Economic Growth In Indonesia In 2005-2024: The Islamic Economic Perspective - Dimas Priadi; Supaijo; Alief Rakhman Setyanto (Nuban Jagadhita Centre, 2026)
Purpose: This study aims to analyze the effect of foreign debt, gold prices, and interest rates on economic growth in Indonesia in the period 2005-2024, both from the conventional side and its suitability in the perspective of Islamic economics. Methodology: This study uses a quantitative approach with secondary time series data, where the Applied Analysis techniques are Vector Error Correction Model (VECM) to identify short-term and long-term relationships, and reinforced with Granger causality test, Impulse Response Function (IRF), and Forecast Error Variance Decomposition (FEVD). Findings: The results of Vector Error Correction Model (VECM) estimation showed that in the short term, foreign debt, gold price, and interest rate had no significant effect on Indonesia's economic growth and did not have a two-way causality relationship based on the Granger test. However, the Johansen cointegration test showed a long-term equilibrium relationship between variables. In the long term, gold prices have a positive and significant effect, interest rates have a negative and significant effect, while foreign debt has a positive but insignificant effect on Indonesia's economic growth. FEVD analysis shows that fluctuations in economic growth in the long term are still dominated by the variable shock itself (self-shock). The novelty of this study lies in the use of up-to-date empirical data coverage until 2024 that successfully captures the dynamics and recovery of the post-pandemic economy, as well as the integration of VECM econometric analysis with critical evaluation of the achievement of falah (ultimate welfare) and distributive justice in Islamic economics.